Digital Marketing Tools that Affect Consumers' Decision to Buy Home Decorations through Online Channels in Samut Sakhon Province - Boonkobkue , Papapat; Maneekool, Chatrpol (Journal of Modern Learning Development, 2023)
The objectives of this research were (1) to study consumers' decision to purchase home furnishings through online channels (2) to study demographic factors, gender, age, education level, occupation, and average monthly income. and (3) to study digital marketing tools that affect the decision to buy home accessories through online channels. It is a quantitative research. (Quantitative Research) The research tool was a questionnaire collected with a sample group of 400 people who used to buy home furnishings online in Samut Sakhon province by using a stratified random sampling method. Are those who have bought home decoration accessories online, have lived in the area of Samut Sakhon for at least 1 year and are ready to answer the questionnaire. The statistics used in the research were frequency, percentage, mean, standard deviation. Independent Sample t-test and Analysis of Variance (ANOVA F-test) and Pearson's Correlation. The results of the study revealed that (1) consumers' decision to buy home furnishings through online channels Overall, it was at the highest level. (2) Demographic factors on education level. and average monthly income different Affecting the decision to buy home furnishings through different online channels of consumers in Samut Sakhon province. statistically significant at the 0.05 level and (3) Digital marketing tools, namely email marketing, search engine optimization (SEO), social media marketing, website (Website) and content marketing affecting the decision to buy home furnishings through online channels. Statistically significant at the 0.05 level.